Exercise testing of elite rowers: comparison of methods and protocols - Mekhdieva, K.; Zakharova, A.; Timokhina, V. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
The aim of the study was to search for appropriate, informative, accessible and reproducible method for testing of elite rowers. Six healthy elite rowers (5 male and 1 female) aged 24±7 underwent two types of exercise testing (ET). Exercise performance of rowers was evaluated by means of: i) standard maximal RAMP cycle test, which is considered to be the gold standard measurement in sports medicine; ii) ET specific for rowers with the use of Concept rowing machine. Both protocols of ET were designed according to International Guidelines for Exercise Testing and Prescription Tests were conducted with simultaneously HR monitoring (Garmin) and breath-by-breathe gas-exchange analysis with the use of desktop metabolic analyzer Fitmate PRO (Cosmed, Italy). A range of physiologic parameters were under consideration: VO2, HR, attained power, minute ventilation and anaerobic threshold (AT). Undertaken comparative analysis demonstrated no significant differences in major analysed physiologic p arameters during both tests. The obtained data enabled us to conclude that cycling ET with the use of maximal ramp incremental protocol is an informative, accessible, reproducible and appropriate method for testing of elite rowers. Conducting both exercise tests - cycling and rowing - may highlight the limiting factors of specific physical workability in rowers.